2018
DOI: 10.1051/shsconf/20184200027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blended learning model on senior high school students’ achievement

Abstract: Abstract. The purpose of this research was to determine the effect of blended learning model on senior high school students' achievement. This study used experimental research method with randomized control group pretest-posttest design. The study was carried out with 63 students attending information and communication technology course, where 31 of whom were in the experimental group and 32 of whom were in the control group. In the experimental group, teacher used blended learning as instructional model, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…In addition, they were able to contribute content and ask questions as well as discuss and debate topics related to their centers of interest. As evidenced by their post-test results, feeling they had a say in their learning experience increased their dedication and engagement (Utami, 2018). Furthermore, the study revealed no significant difference between males and females in the level of the English language proficiency developed, following the treatment.…”
Section: Resultsmentioning
confidence: 78%
“…In addition, they were able to contribute content and ask questions as well as discuss and debate topics related to their centers of interest. As evidenced by their post-test results, feeling they had a say in their learning experience increased their dedication and engagement (Utami, 2018). Furthermore, the study revealed no significant difference between males and females in the level of the English language proficiency developed, following the treatment.…”
Section: Resultsmentioning
confidence: 78%
“…Several recent research results, it was found that Blended Learning has an effect on learning outcomes (Harahap et.al., 2019;Sihabuddin, 2019;Rudiansyah et al, 2019;Surya, 2019;Efgivia, 2019;Hinampas et.al., 2018;Utami, 2018 ;Setyaningrum, 2018;Oweis, 2018;Ekawati, 2018;Fahrurrozi et al, 2017;Isti'anah, 2017;Nouby & Alkhazali, 2017;Kiranawati, 2016;Anggraini, 2016;Daulay et al, 2016;Fardhani, 2016. Through Blended Learning, students are given the opportunity to carry out the learning process so that they are able to understand and manage information, the concept of learning materials is more integrated with various methods, models, and learning styles (Kiranawati, 2016;Sihabuddin, 2019). Blended Learning combines electronic, internet and face-to-face aspects of learning into more open and flexible, occurs anytime, anywhere and with and to anyone in any location (Rudiansyah, 2019;Setyaningrum, 2018;Isti'anah, 2017;Lalima and Dangwal, 2017).…”
Section: A Preliminarymentioning
confidence: 99%
“…Students who are given treatment using BL are able to improve learning outcomes better from pretest to posttest compared to conventional learning (Surya, 2019;Harahap, 2019;Utami, 2018). The practical skills embodied by students are the skills to interpret, communicate, design, record, analyze , and questioning (Hinampas, 2018).…”
Section: B Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations